1978
DOI: 10.2135/cropsci1978.0011183x001800040001x
|View full text |Cite
|
Sign up to set email alerts
|

Issues in Diallel Analysis

Abstract: Critical issues in the use of diallel analysis are reviewed. From a statistical point of view the critical issue concerns the choice of a model with fixed or random genotypic effects. From a genetical point of view, two assumptions are critical in attempts to interpret the resuits of diallel analyses. The assumption concerning the independent distribution of genees in the parents is most critical to proper interpretation and seems to be least acceptable in actual practice. The second assumption, that there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
537
1
32

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 637 publications
(584 citation statements)
references
References 0 publications
14
537
1
32
Order By: Relevance
“…In spite of this, comparison of the many sources, including some recent publications (Baker, 1978;Singh and Paroda, 1984;Pooni et a!., 1984), suggests that some controversy remains, particularly with respect to the choice of design (i.e., including or excluding Sl progenies or reciprocal crosses), the nature of the population whose genetic parameters are being estimated, and the type of analysis to be applied and the assumptions necessary. The purpose of this note is to attempt to clarify some of these issues, drawing freely from earlier literature.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, comparison of the many sources, including some recent publications (Baker, 1978;Singh and Paroda, 1984;Pooni et a!., 1984), suggests that some controversy remains, particularly with respect to the choice of design (i.e., including or excluding Sl progenies or reciprocal crosses), the nature of the population whose genetic parameters are being estimated, and the type of analysis to be applied and the assumptions necessary. The purpose of this note is to attempt to clarify some of these issues, drawing freely from earlier literature.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine which genetic effects (additive or non-additive) had a predominant share in the determination (inheritance) of a given quantitative trait in the progeny, the general predicted ratio (GPR) was estimated for the GCA and SCA effects of the maternal and paternal cultivars. High GPR values, of both maternal and paternal cultivars, for traits such as fruit yield and mean weight of 100 berries indicate the predominance of additive genetic effects over nonadditive effects in the genetic determination of variability in the above-mentioned quantitative traits in the progeny within the parental gene pool (Baker 1978). Earlier studies by Pluta et al (2008a, b), based on an evaluation of F 1 progeny of several dessert blackcurrant cultivars, also showed that the trait of fruit size is mainly determined by additive genetic effects, with very little influence of non-additive effects.…”
Section: Analysis Of Variancementioning
confidence: 99%
“…The breeding value of a parental forms is determined primarily on the basis of the effects of the general (GCA) and specific (SCA) combining abilities of that parental forms _ Zurawicz et al 2006). The GCA of a parent for the trait under consideration determines its ability to pass on the average level of this trait to its progeny (Baker 1978;Vieira et al 2009), and the GCA effect is a measure of the additive effect of the parental genes on this trait (Griffing 1956a, b). The use of parental forms with significantly positive GCA effects for a given trait markedly increases the probability of obtaining hybrid progeny with the desired values of this trait (Bestfleisch et al 2014;Masny et al 2016a, b;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations